2021
DOI: 10.15294/jhe.v6i1.43758
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Anemia Status in Adolescent Girls

Abstract: ABSTRACT   According to Riskesdas 2018, the prevalence of anemia in adolescent girls is very high, at 84.5%. Data from the City of Mataram Health Department in 2017 Puskesmas Selaparang the highest prevalence was 50.43%. Based on the Hb level screening conducted by the Selaparang Health Center, the highest number of anemia in SMAN 9 Mataram was 63 students. The impact of anemia in adolescents, namely decreased reproductive health, decreased learning rates, a height that has not been achieved maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
1
0
1
Order By: Relevance
“…However, in contrast, the research conducted showed a significant relationship between education and eating behavior in preventing anemia (p=0.026). Mulianingsih et al (2021), showed a significant relationship p-value 0.000 between upper-level maternal education and the incidence of mild anemia in adolescents. Based on the theory, highly educated parents will pay more attention to their children's diet because they know the nutritional intake needed by their children.…”
Section: Resultsmentioning
confidence: 92%
“…However, in contrast, the research conducted showed a significant relationship between education and eating behavior in preventing anemia (p=0.026). Mulianingsih et al (2021), showed a significant relationship p-value 0.000 between upper-level maternal education and the incidence of mild anemia in adolescents. Based on the theory, highly educated parents will pay more attention to their children's diet because they know the nutritional intake needed by their children.…”
Section: Resultsmentioning
confidence: 92%
“…Anemia menjadi masalah kesehatan masyarakat global yang utama (Habtegiorgi et al, 2022). Dampak anemia pada remaja adalah kesehatan reproduksi menurun, kecepatan belajar menurun, tinggi badan yang belum optimal, perkembangan motorik berkurang dan terhambatnya kecerdasan otak (Mulianingsih, 2021).…”
Section: Pendahuluanunclassified
“…In particular, it has been observed that higher education levels are associated with better nutritional status in children 34 . Mothers with higher levels of education tend to have broader horizons 35 instructions related to nutritional needs, making it possible for mothers to show reluctance or uncertainty about the importance of nutritional needs to facilitate the growth and development of their children 36 .…”
Section: Overview Of Mother's Education Levelmentioning
confidence: 99%